2012
DOI: 10.3382/ps.2012-02414
|View full text |Cite
|
Sign up to set email alerts
|

Strain and sex effects on growth performance and carcass traits of contemporary commercial broiler crosses

Abstract: In total, 3,840 sexed birds from 6 commercial cross broiler strains (4 male and 3 female) were raised and processed to analyze the effect of strain and sex on growth performance and carcass traits. Chicks from M1 × F1, M2 × F1, M3 × F1, M4 × F1, M3 × F2, and M4 × F3 crosses were sexed. Fifty female and 40 male chicks were randomly allocated to 24 floor pens (119 × 300 cm) covered with pine shavings in each of 4 rooms. The FCR was adjusted for the weight of dead birds (AFCR). Four birds/pen were processed at 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
13
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 28 publications
6
13
0
2
Order By: Relevance
“…Differences in zootechnical performance and carcass traits regarding sex are well documented in broiler chickens. Thus, the improved ADG and FCR as well as higher carcass yield and organ weights in male broilers correspond to data from previous studies (Kidd et al., ; Lopez et al., ; Shim et al., ).…”
Section: Discussionsupporting
confidence: 90%
“…Differences in zootechnical performance and carcass traits regarding sex are well documented in broiler chickens. Thus, the improved ADG and FCR as well as higher carcass yield and organ weights in male broilers correspond to data from previous studies (Kidd et al., ; Lopez et al., ; Shim et al., ).…”
Section: Discussionsupporting
confidence: 90%
“…Estimated parameters for body weight (BW), feed intake (FI), feed conversion ratio (FCR), and body weight coefficient of variation (CV) predictive models of female, male, and straight-run birds, Ross 308 and Ross 708. estimate growth curves for birds raised sex separate. Not surprisingly, in the data presented here, males were heavier followed by straight-run birds and then females, which is consistent with most of the data present in the literature (Smith et al, 1954;Hess et al, 1960;Brake et al, 1993;Gous et al, 1999;May and Lott, 2001;Aggrey, 2002;de Albuquerque et al, 2006;Aggrey, 2009;Shim et al, 2012;Api, 2014;Zuidhof et al, 2014). The growth curve analysis revealed a higher maturity rate and an earlier in life inflection point for the females in comparison with males.…”
Section: Discussionsupporting
confidence: 81%
“…Carcasses that were hard-scalded (60°C for 1.5 min) lost the vast majority of the surface cuticle during defeathering, whereas softscalded (52.8°C for 3 min) carcasses retained the yellow cuticle. Shim et al (2012) recently reported similar hot carcass yield values from 73.5 to 74.5% for 49 d broiler strain crosses for carcasses that were scalded at an intermediate temperature of 54°C and for 120 s. Their broilers had live weighs ranging from 3.08 to 3.39 kg and were the same age and approximate weight (3.12 kg) as our broilers from trial 4 (3.26 kg; Table 1).…”
Section: Resultssupporting
confidence: 57%